Governing urban security in Finland: Towards the 'European model'. (May 2013) - Virta, Sirpa
The article describes and evaluates the development of urban security management in Finland since 2002. The evaluation is based on governmental safety and security strategies, 228 local safety plans from 2002 and the security strategies of the 10 biggest cities in 2012, along with interviews with risk managers or security managers, police chiefs and other experts. New security professions and professionals, such as security managers, have emerged in cities; the trend is towards regional safety and security management; crime prevention has been replaced by a broader concept of the co-production of security by state and municipal authorities (networks, strategic partnerships); contingency planning, civil protection and preparedness have been reconciled with local safety planning processes (in some cities). In addition, the military is looking for a new role in society. It is also argued that European Union membership and EU strategies are now such important drivers of development that Finland is moving from the so-called 'Scandinavian model' towards the 'European model' of security governance.